Механiзми модифiкацiї профiлiв розподiлу домiшок при мас-спектрометричному аналiзi багатошарових наноструктур - Efremov, A. A.; Litovchenko, V. G.; Melnik, V. P.; Oberemok, O. S.; Popov, V. G.; Romanyuk, B. M. (Publishing house "Academperiodika", 2019)
Mechanisms of the spatial redistribution of components in a solid target at its ion bombardment have been analyzed theoretically. The influence of the ion mixing, crater shape, and surface roughness on the results of mass spectrometric measurements is simulated as a function of the ion energy. All the above-mentioned factors are shown to have a minimal impact on the sputtering of nano-sized Mo/Si multilayer periodic structures in the ion energy interval of 200–400 eV. Experimental studies of the dopant depth profiles and their comparison with simulation results allowed us to establish the optimum conditions for the mass spectrometric analysis and to measure the real dopant depth profiles with a depth resolution better than 1 nm.